Respuesta :

we have

[tex]f(x)=(x-3)^{2}(x+2)^{2}(x-1)[/tex]

we know that

The zero of the function is  the value of x when the value of the function is equal to zero

[tex]f(x)=(x-3)^{2}(x+2)^{2}(x-1)[/tex]

rewrite the function

[tex]f(x)=(x-3)(x-3)(x+2)(x+2)(x-1)[/tex]

The zero's of the function are

[tex]x=3\ x=3\ x=-2\ x=-2\ x=1[/tex]

so

[tex]x=3[/tex] ------> has a multiplicity of [tex]2[/tex]

[tex]x=-2[/tex] ------> has a multiplicity of [tex]2[/tex]

[tex]x=1[/tex] ------> has a multiplicity of [tex]1[/tex]

therefore

the answer is

The zero [tex]1[/tex] has a multiplicity of [tex]1[/tex]

The zero [tex]-2[/tex] has a multiplicity of [tex]2[/tex]

From the given function, f(x) = (x − 3)2(x + 2)2(x − 1);

  • The zero 1 has a multiplicity of 1.
  • The zero −2 has a multiplicity of 2

Zeros of a function

The function f(x) = (x − 3)²(x + 2)²(x − 1) given can be expanded so that we have;

  • f(x) = (x − 3)(x-3)(x + 2)(x+2)(x − 1)

Hence, the zeros of the function f(x) are;

  • x = 3, 3, -2, -2, 1

We can conclude that the zero 1 has a multiplicity of 1 and the zero -2 has a multiplicity of 2.

Read more on multiplicity of zeros;

https://brainly.com/question/11314797

ACCESS MORE